Structural identification of graphene films and nanoislands on 6H-SiC(0001) by direct height measurement. (16th April 2023) - Ichou, Hamza; Alchaar, Mohanad; Baris, Bulent; Michon, Adrien; Dagher, Roy; Dujardin, Erik; Martrou, David
Abstract: By combining non-contact atomic force microscopy (nc-AFM) and Kelvin probe microscopy (KPFM) in ultra high vacuum environment (UHV), we directly measure the height and work function of graphene monolayer on the Si-face of 6H-SiC(0001) with a precision that allows us to differentiate three different types of graphene structures : zero layer graphene (ZLG), Quasi free-standing monolayer graphene (QFMLG) and bilayer graphene (BLG). The height and work function of ZLG are 2.62 ± 0.22 Å and 4.42 ± 0.05 eV respectively, when they are 4.09 ± 0.11 Å and 4.63 ± 0.05 eV for QFMLG. The work function is 4.83 ± 0.05 eV for the BLG. Unlike any other available technique, the local nc-AFM/KPFM dual probe makes it possible to directly identify the nature of nanometer-sized graphene islands that constitute the early nuclei of graphene monolayer grown on 6H-SiC(0001) by chemical vapor deposition.